Research on High Speed Dry Cutting Technology and Machining Experiment of Small Module Spiral Bevel Gear - Qi Liu; Hua Zhang; Jianjun Yang (Jixie chuandong, 2021)
Traditional small module spiral bevel gear milling needs to use a large number of cutting fluid，which will not only cause environmental pollution，but also increase production costs，the new technology of high speed dry cutting does not use cutting fluid，which reduces environmental pollution and improves production efficiency. Based on the theory of bevel cutting，combining the equivalent plane method of oblique cutting with the machining theory of spiral bevel gear，the high speed dry cutting technology of small module spiral bevel gear is studied. Aiming at the characteristics of high speed dry cutting technology of small module spiral bevel gear，the thermal mechanical coupling model of bevel cutting is established，and the influence of different process conditions on cutting force is simulated and analyzed by using Abaqus finite element software. The cemented carbide is selected as the tool material，and the high speed dry cutting technology process of small modulus spiral bevel gear is discussed. The feasibility of this technology is verified by machining test. The research provides a reference basis for the implementation of this technology.